Exploring the influence of the critical factors on intentions of employee turnover in the banking segment: a comprehensive mediating analysis - Mohammad Alnehabi; Al-Baraa Abdulrahman Al-Mekhlafi (BMC Psychology)
Abstract The banking sector in Saudi Arabia is integral to achieving the Vision 2030 plan. High employee turnover has been identified as a critical concern, resulting in increasing expenses and lower profitability in the industry. Therefore, a comprehensive investigation is required to determine the variables leading to the high turnover intention and loss of competent employees. This study aims to investigate the relationships between organizational commitment, organizational identification, and employee turnover intention, as well as the mediating roles of employee performance and corporate reputation. A quantitative cross-sectional design was used to collect data from 550 employees in the banking sector through a survey questionnaire. Structural equation modeling was conducted to analyze the data. The findings indicated significant correlations between seven of the eight hypotheses, whereas an insignificant correlation was seen between organizational identification and turnover intention. Furthermore, three mediating associations received partial mediation, and one exhibited full mediation. Model fit indices demonstrated a satisfactory fit, with values below the suggested threshold of 0.08, while the AVE values surpassed the criterion of 0.50. All variables together explained 29% of the turnover intention variance, which met the substantial threshold. The findings demonstrated the importance of these factors in addressing the issue of high employee turnover, which in turn affects the stability and prosperity of the banking industry and, therefore, the Saudi economy as a whole.